First use of the Vibrant Soundbridge middle ear implant in Turkish patients: A report of 2 cases - (:unkn) unknown (MEDITERRANEAN SOC OTOLOGY & AUDIOLOGY, 2007)
The quality and efficacy of conventional hearing aids are limited, and those limitations often cause patients' dissatisfaction and noncompliance. Middle ear implants are a new alternative to conventional hearing aids. The Vibrant Soundbridge (VSB) is an electromagnetic middle ear implant that transforms external sounds into vibrations transmitted directly into the intact ossicular chain. Adult patients (ie, those aged at least 18 years) who have a moderate-to-severe sensorineural hearing loss and who do not benefit from traditional hearing aids because of a medical condition or a device-related problem are candidates for a VSB. Clinical studies have reported overall patient satisfaction with that device, even though the VSB does not seem to be audiometrically superior to conventional hearing aids. Patients have reported satisfaction with the more natural sound quality, lack of feedback, absence of occlusion and distortion, and improved speech discrimination against background noise provided by a VSB. We report the first 2 Turkish patients in whom a VSB was implanted, and we describe our first experience with that device.
Keywords: DEVICE; MULTICENTER